Pengaruh Gender Terhadap Hasil Belajar Matematika Siswa Kelas V SD di Kelurahan Baleharjo - Az Zahra, Muhammad Celvin; Isvandiana Purnamasari, Mega; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2024)
Abstract This researcher has a research objective, namely to find out whether there is an influence of gender on mathematics learning outcomes. This type of research includes quantitative research with ex post facto research. The samples that will be used in this research are SDN 1 Baleharjo and SDN 2 Baleharjo taken with a total of 60 students. Research data was obtained through documentation techniques in the form of student personal data to determine students' names and gender, as well as grade data to determine student learning outcomes. The data analysis technique uses the SPSS version 16.0 program. The results of data analysis concluded that: there is no difference in mathematics learning outcomes between male and female students. This is proven by the sig a results (0.581>0.05) which means there is no difference in learning outcomes between male and female students. Keywords: Gender, Learning Outcomes